A Preliminary Study on the Potential of Virtual Reality Therapy in Reducing Public Speaking Anxiety - Wan Noor Farah, Wan Shamsuddin; Muhammad Nur Adilin, Mohd Anuardi; Intan Syafinaz, Mohmad Rozee (Universidad Cesar Vallejo, 2022)
This study probes on the potentials of Virtual Reality Therapy (VRT) to overcome glossophobia in the context of online classes. To achieve the objective, this study employs experimental design in which students who are enrolled in an online public speaking course were grouped into two: Experimental and control group. The experimental group experienced three sessions of VRT throughout the semester whereas the control group did not. After the end of the course, the descriptive analysis findings suggest that the rate of change for the experimental group was -17% in comparison with the control group -4%. This indicates that the experimental group had decreased their public speaking anxiety four times more than the control group; hence suggesting that VRT has helped to reduce the anxiety in public speaking. All in all, this study foreshadows the great potential of VRT in the education and communication field.